(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to prepare a proposed program in accordance with international auditing standards and based on the laws, regulations and instructions in force, which the auditor must take into consideration when auditing municipal revenues to contribute to improving the process of auditing municipal revenues and assisting auditors in completing auditing procedures with high fluidity and achieving auditing objectives efficiently and effectively. It will be reflected in giving an opinion on the fairness of the financial statements of municipal institutions. The research concluded that the program of the Federal Financial Control Bureau approved for auditing municipal activities did not include detailed auditing procedures for municipal revenues and did not take into consideration international auditing standards. Therefore, the researchers recommend the necessity of adopting the proposed program.